The Use of Acronyms and Abbreviations in Criminal News on Online Media: rakyatbengkulu.com June 2023 Edition - Silvia Sembiring; Lina Tri Astuty Beru Sembiring; Fathiah Indah Syarifah; Novrian Dwi Ramadhan (UNIVED Press, 2020)
The purpose of this research is to describe the abbreviation form and acronym used in the criminal news on Online Media: rakyatbengkulu.com June 2023 edition. This type of research is a qualitative descriptive. The data are taken from the daily issue of rakyatbengkulu.com June 203 edition. The technique of collecting the data is documentation. The results show that, from all 16 data, there are only 4 forms of acronyms and 1 abbreviation form were found in the criminal news on Online Media: rakyatbengkulu.com June 2023 edition. From all three forms of the acronym, there is 2 quotations which represents the first letter of the acronym; there is 7 quotations which represents the first two-letter retention of each component; there is 10 quotations which represents the first three-letter for each component; and there are 12 quotations which represents the retention of many letters and syllables that are difficult to formulate. While on the abbreviation, it is found only the first letter retention of each component as much as 51 quotations. Keyword: Abbreviation, Acronym, rakyatbengkulu.com